Kharīṭat al-mafāhīm li-majālāt al-buḥūth al-jāmiʿiyyah wa-manāhijihā fī Qism Taʿlīm al-Lughah al-ʿArabiyyah - Elhaq, Arini; Bahruddin, Uril; Sutaman, Sutaman (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The confusion of university students in determining the areas of university research and choosing curricula to write it is a real phenomenon. This issue may be due to the lack of clear classification in the fields of university research at a university. This research aims to develop a concept map for the fields of research and its curricula in the Department of Arabic Language Teaching. The researcher used the descriptive analytical approach to the qualitative approach. The study was conducted at the Department of Arabic Language Teaching at STIBA Ar-Raayah. The data was analyzed by collecting data, then sorting the data and then displaying the data, and finally the conclusion. The results of the research indicated that the research areas in the Department of Arabic Language Education at this university are divided into two parts, the first is the educational fields that include education strategies, teaching methods, education programs, education curricula, teaching methods, teaching problems, books or their contents, and evaluation, and the second is language sciences that include lexicography, sociolinguistics, psycholinguistics, grammar, morphology, rhetoric, translation science, phonetics, and language education, and the curricula used in writing research in this department are analytical description method, comparative analytical description method, inductive analytical description method, desk research method, contrastive method, historical analytical description method, and experimental method. The concept map has been systematically developed.